Web services and matchmaking. (1st January 2003) - Field, Simon; Hoffner, Yigal
This paper discusses the need for detailed and comprehensive information models for web services that go a long way beyond currently available models. In this context, the need for this information creates several requirements of the matchmaking facilities needed to find matching business partners. The paper discusses these requirements and provides an assessment of some existing directory and matchmaking facilities. Finally, a working system that addresses these needs is presented.